Особливості будови плодів і онтогенетичного розвитку Tetragonia tetragonioides (Pall.) O.Kuntze (Tetragoniaceae Nakai) - Горлачова, З.С. (Промышленная ботаника, 2004)
The peculiarities of fruit structure and stages of ontogenesis in Tetragonia teragonioides (Pall.) O. Kuntze have been studied. The type of the fruit has been specified: many-stoned pyrenarium with a dry pericarp. Under Donbass’s conditions in ontogenesis only three periods are distinctly pronounced: latent, pregenerative and generative. Peculiarities of ontogenetic development testify to the species being ancient.